2022
DOI: 10.7759/cureus.30937
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of Teleconsultation During COVID-19: A Cross-Sectional Study

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) pandemic created an aberrant challenge for healthcare delivery systems, forcing public health policies across the globe to be shifted from traditional medical care in hospitals to virtual care in the homes of patients. To tackle this pandemic, telemedicine had taken center stage. This study aims to learn about patient satisfaction, feasibility, and acceptability of the use of telemedicine for clinical encounters during the COVID-19 pandemic. MethodologyThis sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…As for the identified studies that were conducted after the pandemic was declared, patients’ and HCPs’ acceptability toward or satisfaction with remote care was high in every case [ 50 - 56 ]. This is in line with previous studies that found a positive attitude toward telemedicine use among patients and HCPs during the pandemic [ 77 , 78 ]. However, such attitudes might have been influenced by the need to adopt remote care technologies imposed by the pandemic [ 65 ], rather than these being an optional alternative.…”
Section: Discussionsupporting
confidence: 93%
“…As for the identified studies that were conducted after the pandemic was declared, patients’ and HCPs’ acceptability toward or satisfaction with remote care was high in every case [ 50 - 56 ]. This is in line with previous studies that found a positive attitude toward telemedicine use among patients and HCPs during the pandemic [ 77 , 78 ]. However, such attitudes might have been influenced by the need to adopt remote care technologies imposed by the pandemic [ 65 ], rather than these being an optional alternative.…”
Section: Discussionsupporting
confidence: 93%